2019
DOI: 10.15761/pmrr.1000195
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between motor and cognitive skills in young basketball players: A bivariate regression analysis

Abstract: The present literature highlights the importance of the cognitive aspects in the motor development of the sporty, Typically Developing children. The cognitive aspects permit to investigate how overcoming our self-limits, by increasing the expectations. The cognitive development is a ground-variable of the motor development, and enriches it.In this study we refer to young basketball players aged between 7 and 11 years old. We propose them a motor (motor manual sequencing skill, manual dexterity, balance, and ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…As a team sport in which each player has a specific task according to their position on the court, it also requires attention while playing with teammates and opponents [ 22 ]. Previous studies have found that the motor competence of young basketball players was positively correlated with cognition (a denomination task and a visuo-spatial working memory task) and motor manual sequencing (ball skills and manual dexterity tasks) [ 23 , 24 ]. As such, basketball could be a good candidate for improving EF in those with IA.…”
Section: Introductionmentioning
confidence: 99%
“…As a team sport in which each player has a specific task according to their position on the court, it also requires attention while playing with teammates and opponents [ 22 ]. Previous studies have found that the motor competence of young basketball players was positively correlated with cognition (a denomination task and a visuo-spatial working memory task) and motor manual sequencing (ball skills and manual dexterity tasks) [ 23 , 24 ]. As such, basketball could be a good candidate for improving EF in those with IA.…”
Section: Introductionmentioning
confidence: 99%
“…This idea is reinforced in the embodied cognition perspective, in which cognition is considered to take place in the context of the sensory-motor interactions of the individual's body with their physical, as well as with their social environment (Barsalou, 1999;Gibbs, 2005;Smith & Gasser, 2005). This theoretical notion is supported by empirical studies (Ludyga et al, 2019;Oberer et al, 2017;Piek et al, 2008;Policastro et al, 2019;Roebers & Kaurer, 2009; that have demonstrated a positive relationship between motor skills and higher cognitive processes such as response inhibition (RI), working memory (WM), and cognitive flexibility (CF), which are collectively known as executive functions (EFs) (Miyake et al, 2000). Previous studies investigating this relationship in typically developing children have yielded inconsistent findings regarding the strength and nature of the association, and while many of the studies examined the association between motor skills and EFs in school children, the extent to which the results can be generalized to preschoolers is still unclear (Cameron et al, 2012;Houwen et al, 2017;Oberer et al, 2017).…”
Section: Introductionmentioning
confidence: 96%